Reappraising the Eclectic Paradigm in an Age of Alliance Capitalism - Dunning, John H. (Journal of International Business Studies, 1995)
This article discusses the implications of the advent of alliance capitalism for our theorizing about the determinants of MNE activity. In particular, it argues that, due to the increasing porosity of the boundaries of firms, countries and markets, the eclectic, or OLI, paradigm of international production needs to consider more explicitly the competitive advantages arising from the way firms organize their inter-firm transactions, the growing interdependencies of many intermediate product markets, and the widening of the portfolio of the assets of districts, regions and countries to embrace the external economies of interdependent activities.